2019
DOI: 10.1029/2019gl082294
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Constraints on the North Polar Cap of Mars from Gravity and Topography

Abstract: The polar ice caps are the largest reservoir of water ice on Mars. The north polar ice cap is composed of the ice‐rich north polar layered deposit (NPLD) and a lower‐lying, silicate‐rich basal unit (BU). Together, these units represent a record of Martian climate history throughout the Amazonian period. Here we place a bulk compositional constraint on the BU by modeling its gravity signature in both spatial and spectral domains using two independent approaches. We find the density of the BU to be 2007+493−445… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…For a heat flow of 20 mW m −2 , the dielectric constant is found to range from 2.40 to 3.15, the elastic thickness is found to be independent of heat flow with a value of at least 330 km, and the density is found to range from 920 to 1,520 kg m −3 . The obtained range of densities is in good agreement with gravity studies at the north (Ojha, Nerozzi, & Lewis, 2019) and south (Wieczorek, 2008;Zuber et al, 2007) poles where the bulk density of both caps was found to be about 1,200 ± 150 kg m −3 .…”
Section: Resultssupporting
confidence: 88%
“…For a heat flow of 20 mW m −2 , the dielectric constant is found to range from 2.40 to 3.15, the elastic thickness is found to be independent of heat flow with a value of at least 330 km, and the density is found to range from 920 to 1,520 kg m −3 . The obtained range of densities is in good agreement with gravity studies at the north (Ojha, Nerozzi, & Lewis, 2019) and south (Wieczorek, 2008;Zuber et al, 2007) poles where the bulk density of both caps was found to be about 1,200 ± 150 kg m −3 .…”
Section: Resultssupporting
confidence: 88%
“…Our findings reconcile and confirm the previous findings of Selvans et al (2010), who argued that the entire BU is very rich in ice, and Lauro et al (2012), who measured a relative permittivity at the top of cavi compatible with a basaltic sand sheet with 41–59% porosity occupied by water ice. Analysis and inversion of gravity signals over Planum Boreum also indicate that water ice makes up more than 50% of the BU by volume (Ojha et al, 2019). Our results on the relative permittivity of cavi indicate abundant excess ice, making this unit one of the largest water ice reservoirs of the planet after the polar layered deposits.…”
Section: Discussionmentioning
confidence: 99%
“…The lithosphere was found to be thick and cold at the north pole, with an elastic thickness of 330–450 km and a surface heat flow of 11–16 mW m2 (see also Phillips et al., 2008). Whereas the long‐wavelength (>400 km) gravity field does not correlate with the surface topography at the north pole (in part because of a poor resolution of the gravity models at high northern latitudes, see also Ojha et al., 2019), the south polar cap shows a clear gravitational signature. It is thus possible to use the gravity field as an additional constraint on the properties of the south polar cap and underlying lithosphere (Ding et al., 2019; Wieczorek, 2008; Zuber et al., 2007).…”
Section: Introductionmentioning
confidence: 99%